A biomimetic cascade nanoreactor for tumor targeted starvation therapy-amplified chemotherapy. (March 2019) - Cheng, Hong; Jiang, Xue-Yan; Zheng, Rong-Rong; Zuo, Sheng-Jia; Zhao, Lin-Ping; Fan, Gui-Ling; Xie, Bo-Ru; Yu, Xi-Yong; Li, Shi-Ying; Zhang, Xian-Zheng
Abstract: Targeted drug delivery with precisely controlled drug release and activation is highly demanding and challenging for tumor precision therapy. Herein, a biomimetic cascade nanoreactor (designated as Mem@GOx@ZIF-8@BDOX) is constructed for tumor targeted starvation therapy-amplified chemotherapy by assembling tumor cell membrane cloak and glucose oxidase (GOx) onto zeolitic imidazolate framework (ZIF-8) with the loading prodrug of hydrogen peroxide (H2 O2 )-sensitive BDOX. Biomimetic membrane camouflage affords superior immune evasion and homotypic binding capacities, which significantly enhance the tumor preferential accumulation and uptake for targeted drug delivery. Moreover, GOx-induced glycolysis would cut off glucose supply and metabolism pathways for tumor starvation therapy with the transformation of tumor microenvironments. Importantly, this artificial adjustment could trigger the site-specific BDOX release and activation for cascade amplified tumor chemotherapy regardless of the complexity and variability of tumor physiological environments. Both in vitro and in vivo investigations indicate that the biomimetic cascade nanoreactor could remarkably improve the therapeutic efficacy with minimized side effects through the synergistic starvation therapy and chemotherapy. This biomimetic cascade strategy would contribute to developing intelligent drug delivery systems for tumor precision therapy.